Spectroscopic characterization of humic substances isolated from sediment of an area of sugarcane cultivation - Pantano, G. [UNESP]; Santos, A. [UNESP]; Bisinoti, M. C. [UNESP]; Moreira, A. B. [UNESP] (Springer Nature, 2013)
Humic substances (HS) have an important environmental property, interacting with metal species and influencing their transport, accumulation, and bioavailability. In this study, the HS of sediment from an area of intensive sugarcane cultivation, considered the third largest in the state of SP, were characterized. This region accounts for about 60% of production in Brazil. The HS were extracted according to the method suggested by IHSS using an alkali extraction, followed by characterization by infrared spectroscopy (IR), ultraviolet/visible (UV/Vis) spectroscopy, and molecular fluorescence. The IR spectra showed characteristic bands of HS, and the E4/E6 ratio obtained in the UV/Vis analysis was <5, suggesting a more condensed structure. The results obtained in the emission molecular fluorescence spectra also showed characteristics of predominantly aromatic structures. In the synchronous molecular fluorescence, highest fluorescence intensity was in the region of 400 nm, which is assigned to aromatic polycyclic hydrocarbons with five aromatic rings. Thus, the results showed that the humic substances have a molecular structure with a higher degree of condensation, having thus more aromatic structures than aliphatics.
Keywords: Characterization; E4/E6 ratio; Humic substances; Infrared; Molecular fluorescence